Efficacy of Mepolizumab in the Treatment of Severe Asthma with a Mixed Granulocytic Pattern of Airway Inflammation (Case Report) - A. M. Gubareva; S. V. Fedosenko; D. A. Vinokurova; S. V. Nesterovich; E. S. Kulikov; D. V. Polyakova; E. A. Starovoitova (Архивъ внутренней медицины)
This article describes two clinical observations of the use of mepolizumab in patients with severe uncontrolled asthma with a mixed granulocytic pattern of inflammation in the bronchi and comorbid pathology. The mixed granulocytic form of severe asthma is characterized by a combination of T2 endotype and non-T2 endotype. The most common mixed granulocytic pattern of severe asthma occurs in comorbid pathology, in particular, when it is combined with chronic obstructive pulmonary disease (COPD) or bronchiectasis.In the presented observations, both patients had an experience of smoking, a late manifestation of bronchial asthma with the development of centrilobular emphysema and an irreversible decrease in the FEV/FVC ratio as part of the development of COPD. A feature of one of the cases was the presence of cylindrical bronchiectasis in both lungs. The choice of mepolizumab as an additional maintenance agent at GINA stage 5 in both cases was justified by the uncontrolled course of asthma despite the use of a high dose of glucocorticosteroids in combination with other basic drugs and the need for the use of systemic corticosteroids > 50 % of the time per year, a history of recurrent exacerbations in previous 12 months, the presence of persistent blood eosinophilia (>150 cells/μl), as well as a combination of asthma with polypous rhinosinusitis in one of the patients.Overall, the use of mepolizumab 100 mg subcutaneously every four weeks in addition to regular maximum optimized maintenance therapy was characterized by rapid, signifi cant and sustained effi cacy, which was expressed in early achievement of asthma control within the fi rst 16 weeks of therapy.